(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate epidemiological, clinical characteristics, and prognostic factors after curative gastrectomy for gastric cancer at the Transport Hospital. Methods: A retrospective cross-sectional study was conducted on 154 patients diagnosed and surgically treated for gastric cancer between January 2020 and November 2024. Demographic, clinical, laboratory, and pathological data were collected. Survival was analyzed using Kaplan–Meier and multivariate Cox regression to identify prognostic factors. Results: The mean age was 61.7 ± 9.8 years, with 66.2% male patients. Most cases were diagnosed at advanced stages (II–III). Poor general condition (ASA ≥3), low serum albumin, and preoperative anemia were significantly associated with higher postoperative complications and shorter survival (p<0.05). Cox regression confirmed disease stage and nutritional status as independent prognostic factors. No 30-day mortality was observed, and the overall complication rate was 14.3%. Conclusion: Disease stage and general condition remain the strongest prognostic indicators in gastric cancer patients. Curative surgery is safe and effective in this setting; however, early detection and preoperative nutritional optimization are essential to improve long-term outcomes.